The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jopr.13522
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Post and Core Fabricated with Digital Technology

Abstract: To compare the accuracy of post and cores created with three different fabricating techniques: direct conventional, machine milling, and three-dimensional (3D) printing. Materials and methods:Thirteen extracted single root central incisors were selected. Root canal treatment and tooth preparation for crown were performed on all teeth. Post space preparation of 11 mm was created using prefabricated fiber post drill to standardize post space width and length. Root canal impressions were performed on all teeth us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Consequently, it can be assumed that 3D printing post and core resulted in a post and core with reduced accuracy. This was reported in a previous article that found that 3D printed post and core was not as accurate as milled post and core 9 . This problem has also been observed in 3D printed complete dentures, removable partial dentures framework, and crowns when compared to the milling technique 16–18 .…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Consequently, it can be assumed that 3D printing post and core resulted in a post and core with reduced accuracy. This was reported in a previous article that found that 3D printed post and core was not as accurate as milled post and core 9 . This problem has also been observed in 3D printed complete dentures, removable partial dentures framework, and crowns when compared to the milling technique 16–18 .…”
Section: Discussionmentioning
confidence: 74%
“…This study evaluated the accuracy of 3D printed post and core using different materials by measuring the volume of each post and core with digital software. The volume measurement method has been reported in a previous article 9 . Post and core with more volume can be assumed to have better accuracy and better adaptability as it would mean less gap between the root canal and post.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the fact that fiber posts are prefabricated has caused problems in their adaptability with the morphology of the root canal [2]. In this way, CAD/CAM posts that combine the intra-canal adaptability of cast metal posts and the elastic modulus of fiber posts to dentin have come to the fore and have been introduced to the market [4,5].…”
Section: Introductionmentioning
confidence: 99%